STAPHYLOCOCCUS AUREUS RESEARCH AND QUALITY ANALYSIS OF FRESH HOMEMADE MILK SOLD IN THE CITY OF ANÁPOLIS - GO (CIPEEX, 2025)
This study analyzes the microbiological and physicochemical quality of homemade fresh milk sold in Anápolis, Brazil, with a focus on the detection of Staphylococcus aureus, a pathogenic microorganism associated with foodborne intoxications. The research aims to identify possible failures in hygiene practices during milking and storage, while also comparing the results with the standards established by Brazilian legislation. Over the course of one year, samples will be collected from different properties and informal sale points and subjected to physicochemical analyses (pH, acidity, density, fat, protein, cryoscopy, and water activity) as well as microbiological tests (mesophilic bacteria, coliforms, yeasts, molds, and S. aureus using Baird-Parker selective medium and confirmatory assays). The expected findings include variations in physicochemical parameters and the presence of S. aureus in some samples, which may indicate risks to public health. This study concludes that the generated data can support educational initiatives and raise awareness among both producers and consumers about the importance of hygienic practices in dairy production. Furthermore, the results may contribute to reinforcing sanitary control strategies and ensuring safer consumption of artisanal milk products.